A clue in a colour? EBUS-TBNA in the analysis of isolated mediastinal lymphadenopathy. (23rd February 2014) - Ryan, Daniel John; McPhillips, Dympna; Bruzzi, John; Breen, David
Abstract : A 52-year-old female patient with a background history of malignant melanoma was referred to the interventional pulmonology unit at Galway University Hospital for the investigation of possible intrathoracic recurrence. A CT of the thorax (CT thorax) demonstrated mediastinal lymphadenopathy at position 4R, right paratracheal region. An endobronchial ultrasound (EBUS) revealed multiple enlarged lymph nodes at station 4R. The nodes were heterogeneous with solid and cystic elements. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) obtained a black material consistent with malignant melanoma. Multiple TBNA samples were obtained and the diagnosis was confirmed pathologically by the presence of multiple epithelioid pigmented cells on cell block analysis. This case report emphasises the value of EBUS in the assessment of metastatic disease and, in particular, how the gross appearance of the sample can be suggestive of the diagnosis.